PELATIHAN KOMPUTERISASI DAN TRANSFORMASI SISTEM YANG ERGONOMIS DENGAN PENDEKATAN KOGNITIF ON-THE-JOB KEPADA KARYAWAN PT.XTZ - Pandena Kicky Basuki Putri; Darmawan Yudhanegara (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The goal of on-the-job training with a cognitive ergonomics theme in a wood company is to improve employee performance, health, and safety by integrating cognitive ergonomics principles into their work between man and computer in ERP system workstation. In this training, employees will learn about managing cognitive load and adapting their work environment to support their cognitive performance on the job directly. By integrating cognitive ergonomics into on-the-job training, the wood company can ensure that employees can adapt to their work environment more quickly and effectively while also applying cognitive ergonomics principles to improve their performance. Ultimately, this will help the company achieve its goals more effectively and efficiently while improving the quality of work and employee satisfaction. Training result after two months made work perfomance increase from 0,43 to 0,47.